Adaptive information management system of dynamic monitoring of actual water content in jet fuel in technological processes of aviation fuel supply - A. A. Brailko; V. M. Samoylenko; N. A. Druzhinin; L. A. Druzhinin (Научный вестник МГТУ ГА)
Modern domestic and international standards, regulators of the aviation fuel industry, considering the negative impact of the presence of mechanical impurities and water in aviation fuel on the performance and life cycle of aircraft engines, fuel metering equipment, fuel systems of aircraft (A/C), as a threat factor for flight safety, impose high requirements for the purity of aviation fuel while operating aeronautical equipment. At the same time, the causes and sources of water content in jet fuel are a source of economic losses, the most important criterion for the success of the Aerodrome Fueling Complex business. The article considers the task of developing reliable and automated methods as well as technologies for controlling these contaminants, for example for determining water content in aviation fuel when refueling aircraft, and the necessity to minimize an effect of a human factor. The automation of aviation fuel quality monitoring processes, the transition from discrete control methods to continuous ones, from static control methods to dynamic ones (in-line), from indirect methods to direct ones are becoming relevant. The possibilities of end-to-end accounting and analysis of aviation fuel purity parameters at all stages of the aviation fuel life cycle are shown. The article considers the methods and conducts the analysis of known techniques and devices used to determine, measure and indicate actual water content, presence of dissolved, free and total water in jet fuel. The technical solution of continuous automated control of the actual water content level of the jet fuel flow in the processes of aviation fuel supply and aircraft refueling in an information system that provides on-line monitoring and dynamic measurement of the quantitative content of dissolved and free water in the jet fuel flow, is presented. The technical solution for the continuous determination of the quantitative water content in the jet fuel stream is proposed. At the same time, the solution of the problem of monitoring water content in jet fuel is combined with the technological process to control the purification of jet fuel from water. The paper represents an adaptive information management system for continuous monitoring of the water content level of the jet fuel flow, which will allow specialist to substantially increase a level of automatization of aircraft aviation fuel supply technological processes, decrease a negative impact of a human factor, increase economic effectiveness of the aviation fuel supply complex. The system is designed to carry out continuous, automated control (monitoring) of water content in the jet fuel flow at all the stages of the jet fuel movement: receiving, storing and delivering jet fuel and refueling aircraft, in particular fuel and lubricants warehouses (fuel and lubricants), refueling complexes and pre-apron filling points. It can also be used in the fuel system of the aircraft, as a system to prevent water content in the jet fuel. The integration of automation tools will enable us to improve the quality of management of aviation fuel supply and aircraft refueling to ensure timely operational decision based on real data in real time mode, provided the proposed system integration into the airport system for operational data exchange.